Supplementation with myo-inositol and Selenium improves the clinical conditions and biochemical features of women with or at risk for subclinical hypothyroidism - Payer, Juraj; Jackuliak, Peter; Kužma, Martin; Džupon, Matúš; Vaňuga, Peter (Frontiers in Endocrinology, 2022)
The depletion of myo-Inositol is involved in the thyroid stimulating hormone (TSH) signaling pathway and is frequently associated with the onset and development of thyroid diseases such as hypothyroidism. Particularly, subclinical hypothyroidism is a pathological condition characterized by altered TSH values and thyroid hormones within the normal reference range. This condition might be combined or not with auto-immune issues. Patients affected by subclinical hypothyroidism exhibited a significant improvement of their condition when treated for 6 months with a combination of myo-Inositol and Selenium. The TSH values significantly ameliorated along with the index of autoimmunity and the thyroid status. In a sub-class of patients, the auto-antibody titer decreased after myo-inositol + Selenium administration. The treatment also induces a regularization of the menstrual cycle and a reduction of the cholesterol in the patients enrolled for the study. Furthermore, a significant improvement is observed in the perception of the symptoms associated with subclinical hypothyroidism over the treatment period. The aim of this study is to describe the beneficial role of myo-Inositol and Selenium in the treatment of patients affected by subclinical hypothyroidism.